INCIDENCE AND PREVALENCE OF PRIMARY SCLEROSING CHOLANGITIS: A META-ANALYSIS OF POPULATION-BASED STUDIES. (22nd January 2022) - Cooper, Jared; Markovinovic, Ante; Coward, Stephanie; Shaheen, Aziz; Swain, Mark; Panaccione, Remo; Ma, Christopher; Novak, Kerri; Kaplan, Gilaad
Abstract: BACKGROUND: Primary sclerosing cholangitis (PSC) is a chronic liver disease associated with significant morbidity, mortality and healthcare utilization—with nearly 80% of PSC patients having inflammatory bowel disease (IBD). Understanding the incidence of PSC is important in defining the burden of disease and planning for allocation of healthcare resources. AIM: To conduct a systematic review and meta-analysis of population-based studies of the incidence and prevalence of PSC in the general population and in IBD. METHODS: Medline and Embase (from inception to May 10, 2021) were systematically searched to identify studies via the following inclusion criteria: 1) original articles, 2) population-based study of defined geographic area, 3) reported the incidence or prevalence of PSC in the general population. Studies that assessed specific populations (e.g., pediatric-only) were excluded. Abstracts and full texts were reviewed for inclusion and data was extracted independently in duplicate by two individuals (JC, AM). Meta-analyses, using random-effects, were performed to calculate overall and country-specific incidence and prevalence rates (per 100, 000 persons) with 95% confidence intervals (CI). Meta-analysis pooled the Average Annual Percentage Change (AAPC) in the incidence of PSC in the general population. RESULTS: The initial search returned 3, 958 abstracts. After duplicates were removed, abstracts (3, 443) were screened, and full texts were reviewed (317), 17 studies met the criteria for inclusion for incidence and 19 for prevalence in the general population. Studies originated from 13 countries from North America, Asia, Europe, and Oceania (Figure 1). In the general population, incidence rates and prevalence of PSC was 0.75 (95% CI: 0.542, 1.05) and 11.16 (95%CI: 7.78, 16.02) per 100, 000 persons, respectively (Figure 1). Incidence rates of PSC were significantly increasing overtime (AAPC: 4.56%; 95% CI: 0.45, 8.68). DISCUSSION: The incidence of PSC is low at 0.75 per 100, 000 but has been significantly increasing over time. The prevalence of PSC is low at 11.16 per 100, 000 in the general population. Future studies on the incidence and prevalence of PSC in the general should be directed at Asia, Africa of Latin America to allow for a more robust assessment of the global epidemiology of PSC.